2016
DOI: 10.2196/mhealth.4569
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Health Promotion via Text Messaging at a Community Health Center in South Africa: A Mixed Methods Study

Abstract: BackgroundThe use of mobile phones to deliver health care (mHealth) is increasing in popularity due to the high prevalence of mobile phone penetration. This is seen in developing countries, where mHealth may be particularly useful in overcoming traditional access barriers. Non-communicable diseases may be particularly amenable to mHealth interventions, and hypertension is one with an escalating burden in the developing world.ObjectiveThe objective of this study was to test whether the dissemination of health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 13 publications
0
54
0
1
Order By: Relevance
“…In agreement with our findings, Leon et al [30] showed that weekly texts were acceptable for persons with hypertension. Hacking et al [31] also found a positive attitude toward this intervention in patients with hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with our findings, Leon et al [30] showed that weekly texts were acceptable for persons with hypertension. Hacking et al [31] also found a positive attitude toward this intervention in patients with hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…Mobile health (mHealth) messaging programs have rapidly increased in LMIC and provide a means to support self-management programs especially needed for NCDs. A number of studies have focused on short message service (SMS) text messaging to improve outcomes for hypertension [10,11] and diabetes [11,12-14]. While these studies have generally shown messaging to be an acceptable format to participants, results have been mixed, with several showing small changes in some disease outcomes [10,12-14] or behavioral change [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Davey et al, (2018) the success of treatment requires the support of text messages sent weekly or daily or a combination of counseling and text messaging. Text reminder messages as a condition for action act as a reminder in changing health behavior, self-management, increasing patient self-efficacy through drug reminders with motivational text messages (Hacking et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, the SMS reminder given to hypertensive patients did not affect health knowledge. But it influences positive behavior changes, so effective reminder messages act as reminders to change with motivational content rather than providing health information (Hacking et al, 2016). At the individual level, self-efficacy is an interpersonal part that influences behavior change (Rimer & Glanz, 2005).…”
Section: Discussionmentioning
confidence: 99%